Inhibition of Bacterial Growth and Intramniotic Infection in a Guinea Pig Model of Chorioamnionitis Using PAMAM Dendrimers - Wang, Bing (2010)
Dendrimers have emerged as topical microbicides to treat vaginal infections. This study explores the in-vitro, in-vivo antimicrobial activity of PAMAM dendrimers, and the associated mechanism. Interestingly, topical cervical application of 500 µg of generation-4 neutral dendrimer (G(4)-PAMAM-OH) showed potential to treat the Escherichia coli induced ascending uterine infection in guinea pig model of chorioamnionitis. Amniotic fluid collected from different gestational sacs of infected guinea pigs post treatment showed absence of E. coli growth in the cultures plated with it. The cytokine level [tumor necrosis factor (TNFα) and interleukin (IL-6 and IL-1β)] in placenta of the G(4)-PAMAM-OH treated animals were comparable to those in healthy animals while these were notably high in infected animals. Since, antibacterial activity of amine-terminated PAMAM dendrimers is known, the activity of hydroxyl and carboxylic acid terminated PAMAM dendrimers was compared with it. Though the G(4)-PAMAM-NH(2) shows superior antibacterial activity, it was found to be cytotoxic to human cervical epithelial cell line above 10µg / mL, while the G(4)-PAMAM-OH was non cytotoxic upto 1mg / mL concentration. Cell integrity, outer (OM) and inner (IM) membrane permeabilization assays showed that G(4)-PAMAM-OH dendrimer efficiently changed the OM permeability, while G(4)-PAMAM-NH(2) and G(3.5)-PAMAM-COOH damaged both OM and IM causing the bacterial lysis. The possible antibacterial mechanism are; G(4)-PAMAM-NH(2) acts as polycation binding to the polyanionic lipopolysaccharide in E. coli, the G(4)-PAMAM-OH forms hydrogen bonds with the hydrophilic O-antigens in E. coli membrane and the G(3.5)-PAMAM-COOH acts as a polyanion, chelating the divalent ions in outer cell membrane of E. coli. This is the first study which shows that G(4)-PAMAM-OH dendrimer acts as an antibacterial agent.